Resepsi Estetis Terhadap Seni Baca Al-Qur’an di Majelis Tilawah Al-Qur’an Ummul Qura Sungai Lulut Kabupaten Banjar - Najib Irsyadi; Warliza Warliza; Ahmad Mujahid (Sekolah Tinggi Agama Islam Al Washiliyah Barabai, 2024)
In the lives of Muslims, there are many practices of reception of the Al-Qur'an, both in the form of reading, understanding, practicing it and in the form of socio-cultural reception. In South Kalimantan, many people are found who receive, respond to or treat the Al-Qur'an by reading it and singing it or what is usually called the art of reading the Al-Qur'an. This is proven by the productivity of South Kalimantan in producing national and international qari'ah. This research aims to examine further the aesthetic reception of the art of reading the Qur'an and the process of training in the art of reading the Qur'an by taking place, namely the Ummul Qura Al-Qur'an Recitation Council which is in Sungai Lulut, Sungai Tabuk District, Regency. Banjar is a place to learn the art of reading the Koran, especially vocals and songs, which has produced many national and international reciters. This type of research is field research using descriptive qualitative methods. Data collection techniques were carried out using observation, interviews and documentation. The results of the research found that all the reciters in the Al-Qur'an Recitation Council Ummul Qura received the Al-Qur'an by reading it with songs. Departing from this aesthetic reception produces very diverse effects. This is because the aesthetic reception of the Al-Qur'an has a psychological interest that can invite reactions to awaken the reader's mental energy. The authors grouped the effects they felt into four aspects, namely emotional and spiritual aspects, functional aspects, beneficial aspects and habitual aspects. In this research the author discovered something unique, namely that the aesthetic reception of the art of reading the Qur'an can give birth to other reception patterns such as functional reception as actualized by several reciters in the Ummul Qura Al-Qur'an Recitation Council.